Variante nordestina na Educação de Jovens e Adultos: a visão do aluno - Anjos, Rosangela Xavier dos (2008)
The purpose of this work is to present, under a Sociolinguistic point of view, contemporary theories regarding linguistic variation, having the Brazil northeastern variant as spoken by the students of Educação para Jovens e Adultos school (E.J.A.). The research has as sample to investigation, interviews given by Brazil northeastern students and its proposal is to observe the northeast vocabulary as a way of expression of the northeast culture and customs. The main objective is to verify the treatment given to the northeastern variant on classroom, as seen from the student s perspective. To meet the ends of this research, the interview method was chosen, aiming at getting elucidative data to the present work. The field task is performed by means of recording individual interviews with the E.J.A´s northeastern students. It was verified, through the research, that there is a linguistic richness and peculiarity on E.J.A, most of all, as regards to people immigration from Brazil northeastern different states. The northeast variant is part of a linguistic reality, being in that way, an object of study, because it is present at the most different scholarship contexts